Probenecid Inhibits Platelet Responses to Aggregating Agents in Vitro and Has a Synergistic Inhibitory Effect with Penicillin G - Packham, M A; Rand, M L; Perry, D W; Ruben, D H; Kinlough-Rathbone, R L (Thrombosis and Haemostasis, 1996)
Probenecid is an anion channel blocker and uricosuric agent, originally developed to slow the rate of excretion of penicillin. It is now also administered with many other drugs to reduce their required dosages. Recently, probenecid (2.5 mM) has been used to prevent leakage of fura-2 or fluo-3 when these indicators of cytosolic Ca2+ levels have been introduced into cells. However, we found that probenecid markedly inhibited the increases in cytosolic Ca2+ caused by ADP, thrombin, the thrombin receptor-activating peptide (SFLLRN, TRAP), ADP, sodium arachidonate, the thromboxane A2 (TXA2) mimetic U46619, and platelet-activating factor (PAF). This finding precluded the use of probenecid with platelets in measurements of cytosolic Ca2+ with indicators such as fura-2. We then investigated the effects of probenecid on aggregation and release of 14C-serotonin from prelabeled platelets. Responses to all the agonists were inhibited by 2.5 mM probenecid, but concentrations as low as 0.25-0.5 mM inhibited responses to agonists that act largely via TXA2 (collagen, sodium arachidonate and U46619). Collagen-induced TXA2 formation was inhibited in a dose-dependent manner. Responses of aspirin-pretreated platelets to thrombin, SFLLRN, U46619 and PAF were also inhibited by probenecid, indicating that prevention of TXA2 formation does not account for all the inhibitory effects. The combination of probenecid with penicillin G produced additive or synergistic inhibition of platelet responses; responses dependent on TXA2 were synergistically inhibited by concentrations of the drugs that are reached in vivo. The synergistic inhibitory effect of probenecid on platelet functions could further impair hemostasis if it has already been partially compromised by the administration of other drugs.